MUSIC RADIO AND GLOBAL MEDIATION. - Tucker, Joshua (Cultural Studies, 2010)
This article offers a model for studying the dynamics of globalized popular musics, that fills methodological and theoretical lacunae in existing scholarly approaches. It deals with the emergence and circulation of a hybrid popular music called musica ayacuchana, which over the 1990s became an important site of identification for the emergent Andean migrant middle class of Lima, Peru. Describing the role of radio stations and, particularly, DJs' actions in this process, I suggest that attention to the working practices of mediators can reveal how popular music becomes attached to new identities, particularly in the context of broader social changes. Further, I use this example to show why scholarly accounts of globalization, which rarely attend to the everyday mechanics of mediation, must take them into account, to arrive at a satisfactory understanding of the way that these processes engage, challenge, and/or reproduce social hierarchies.